The Relationship between Self-efficacy and Goal setting in Student Sepak Takraw Athletes in Indonesia - Tasyafa, Fadia; Kusumawardani, Dianti Endang (Institut Teknologi Bandung, 2025)
Self-efficacy and goal setting were psychological factors that influenced athletes in improving sports performance. This study aimed to determine the relationship between self-efficacy and goal setting in student Sepak Takraw athletes in Indonesia. The instruments used were the Athlete Self-Efficacy Scale (ASES) (Koçak, 2020) and the Self-Audit Questionnaire for Goal Setting (Wilson & Dobson, 2008). Data collection was carried out using the convenience sampling technique. The study involved 156 Sepak Takraw athletes aged 12-18 years. Descriptive statistical analysis was used to describe the levels of self-efficacy and goal setting among Sepak Takraw athletes, while Spearman correlation analysis was conducted to examine the relationship between the two variables. The results indicated that 66.03% of athletes had a moderate level of self-efficacy, while goal setting was also categorized as moderate, with a percentage of 75.64%. The relationship between self-efficacy and goal setting showed r = 0.638 (p < 0.001), indicating a significant relationship with a strong correlation between these two variables in student Sepak Takraw athletes in Indonesia. The findings of this study can be applied in training programs by optimizing self-efficacy and goal setting, such as implementing the SMART method (Specific, Measurable, Achievable, Relevant, Time-bound) as a strategy to enhance athlete performance.